Zero Information Practice: The Foundation of Spiritual Experience - Doner, Jonathan (The international journal of religion and spirituality in society, 2015)
This paper examines two significant problems in the study of spiritual experience—its nature and its relation to normal experience. Is spiritual experience completely distinct, i.e., sui generis, or is it a variation of normal experience, that is then ascribed a spiritual or religious character? The present work uses an information-based approach to shed new light on this issue. As a consequence, it provides a new, objective characterization of the necessary conditions for the occurrence of spiritual experience.